(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: In patients aged 60-80 years, the decision between internal fixation and arthroplasty remains controversial due to various factors like age, impaired mobility, poor balance and delayed reaction time. We conducted this study to see the outcomes of early surgical intervention in femoral neck fractures in the elderly patients and to compare the results of fixation and replacement. Materials & Methods: Patients with fracture neck of femur over age of 60 who went under early surgical intervention were selected retrospectively. These surgically treated patients were divided into 2 groups: fixation and replacement. In Fixation group, 3 patients were treated with cannulated cancellous screws and 22 with mini dynamic hip screws, whereas in replacement group 54 were treated with partial hip replacement and 21 with total hip replacement. Post operatively patients were assessed with modified barthel’s index (MBI), harris hip scores (HHS), SF-36 scoring & visual analouge scale (VAS) at discharge, 6 weeks, 3 months, 6 months and 1-year follow-up visits. Results: The patients undergoing arthroplasty having had a 1.5 times better modified barthel’s index score compared to fixation at 1 year. The harris hip scores had a 1.7 times better score compared to fixation at 1 year. All 9 sub-components of harris hip scores, all 8 sub-components of SF-36 questionnaire as well as range of motions sub-components at discharge v/s 6 months & discharge v/s 1 year when compared, showed a significantly higher score in both arthroplasty & fixation patients at 6 months & 1 year compared to scores at discharge. Conclusion: Functional outcomes were better in the patients treated with arthroplasty compared to fixation of the neck femur fracture over a 1 year period in the elderly population in India.